IN PARTICULAR THE LEVEL OF QUALITY IN THE PERSIAN AND UZBEK LANGUAGES (American Journal of Pedagogical and Educational Research, 2023)
This article provides information about Uzbek suffixes used in boburn, such as most, very, very many. When the author adds the suffix -rak to several Persian words, he also uses words that belong to the category of Persian nouns, i.e. ob + cancer, not adjectives. Semantically, quitrent can mean "more watery". The play also actively uses suffixes meaning -tar (-roq), -tarin (the most, very, kind), which are an indicator of the level of quality in the Persian language. The bottom line is that Boburnoma uses the indicators of the Persian and Uzbek languages. We see that the suffix -raq (-rak) is mainly used in Persian, Uzbek and Arabic synonyms.